Faktor-Faktor Yang Memengaruhi Rendahnya Penggunaan KB IUD di Puskesmas Gunting Saga Kecamatan Kualuh Selatan Kabupaten Labuhan Batu Utara Tahun 2023 - Leni Br Sarumpaet; Nur Azizah; Lidya Natalia Sinuhaji; Debby Chintya Yun (The Journal General Health and Pharmaceutical Sciences Research, 2025)
Background: Stunting is a chronic nutritional problem in children under five years old caused by inadequate nutritional intake and recurrent infections, especially in the First 1000 Days of Life (HPK). Exclusive breastfeeding and maternal nutritional knowledge are key factors that influence the incidence of stunting. Indonesia faces a high prevalence of stunting, which can impact the quality of human resources in the future if not addressed immediately. Objective: This study aims to determine the relationship between maternal nutritional knowledge and the duration of exclusive breastfeeding with the incidence of stunting in infants aged 6–12 months in the working area of ​​Kuala Bangka Health Center, Kualuh Hilir District, North Labuhan Batu Regency in 2021. Method: This study used a case-control design with a sample of 110 respondents (55 cases and 55 controls) selected by purposive sampling. Data were collected through interviews using a structured questionnaire and analyzed using the Chi-Square test. Results: The results showed a significant association between the duration of exclusive breastfeeding and the incidence of stunting (p = 0.002; OR = 4.394; 95% CI = 1.709–11.295), where infants who were not exclusively breastfed had a 4.4 times greater risk of experiencing stunting than infants who received optimal exclusive breastfeeding. However, there was no significant association between maternal nutritional knowledge and the incidence of stunting (p = 0.233). Conclusion: The duration of exclusive breastfeeding was proven to be associated with the incidence of stunting, while maternal knowledge did not show a significant association. Stunting prevention efforts should focus on improving the practice of appropriate and comprehensive exclusive breastfeeding, accompanied by practice-based nutrition education that mothers can apply in childcare.